(untitled) (London Journal of Medical and Health Research, 2026)
Introduction: Nutritional recommendations for patients with T2DM from various global communities agree on the need to increase dietary fiber (DF) intake; however, there are currently no specific and unified recommendations regarding the recommended amount and type of DF. Studying the effect of DF on glycemic control in patients with T2DM may play an important role in refining intake recommendations and motivating patients to comply these recommendations. Objective of the Study: Evaluation of the effect of Nestlé OptiFibre DF on glycemic control parameters in patients with T2DM treated with combination hypoglycemic therapy with metformin plus dipeptidyl peptidase-4 inhibitors (DPP-4 inhibitors) or with metformin plus sodium-glucose cotransporter type 2 inhibitors (SGLT2 inhibitors). Materials and Methods: The study included 80 patients with T2DM, with duration not more than 5 years, with HbA1c of not more than 7.5%, and BMI of 27–35 kg/m2, without severe comorbidity. All patients were treated with a combination of metformin and a DPP-4 inhibitor or metformin and an SGLT2 inhibitor. Forty patients comprised the Main Group, where patients received Nestlé OptiFibre DF, a partially hydrolyzed guar gum (PHGG), for 3 months according to the instructions for use. The other patients, who comprised the Control Group, underwent the same examinations as the patients in the Main Group as part of routine clinical practice over a period of 3 months. Changes over time in HbA1c, fasting plasma glucose, blood glucose self-monitoring data, and ambulatory blood glucose profile based on flash glucose monitoring (FGM, FreeStyle Libre, Abbott) were evaluated. Laboratory parameters were evaluated at baseline (2–3 days from the start of the study) and at the completion of the study (84 ± 3 days from the start of the study). A FGM sensor was also applied at Days 2–3 from the start of the study; the readings were obtained and evaluated after 14 days. Repeated FGM application was performed at Day 72 ± 3, and the readings were obtained at Day 84 ± 3. Results: In the group of patients who received DF, there was a statistically significant decrease in the HbA1c level from 6.35 [5.9–7.07]% to 5.95 [5.7–6.3]%, p = 0.01, while in the Control Group almost no changes were found: at baseline, the HbA1c level was 5.85 [5.5–6.7]%, and at study completion it was 6.15 [5.5–6.78]%, p = 0.99. Fasting plasma glucose in the Main Group decreased from 7.0 [6.33–7.78] mmol/L to 6.65 [5.72–7.75] mmol/L, p = 0.18, while in the Control Group, on the contrary, an increase this parameter increased from 6.30 [5.7–7.0] mmol/L to 6.9 [5.6–7.78] mmol/L, p = 0.05. The evaluation of the ambulatory glucose profile (AGP) data showed that the Time in Range (TIR) was significantly higher by the end of the study in the Main Group vs the Control Group by 2.5%: 94.5 [92.0–97.0]% vs 92.0 [77.25–96.0]% (p = 0.01). Time Below Range (TBR) in the Main Group decreased by 0.5% while no changes were observed over time in the Control Group, and the increase in Time Above Range (TAR) in the Main Group was 0.5% lower than in the Control Group. In addition, a decrease in the mean duration of hypoglycemia was found in patients who received DF, from 144.39 ± 76.49 (95% CI 115.87; 172.91) to 118.32 ± 54.49 (95% CI 96.81; 139.84), p = 0.15, as well as a decrease in the frequency of hypoglycemic events from 6.0 [3.0–16.0] to 5.0 [3.0–9.75], p = 0.47. Conclusions:The study obtained data on the positive effect of daily intake of PHGG for 3 months on the HbA1c, fasting plasma glucose and AGP parameters, which is important not only from the point of view of managing T2DM, but also from the standpoint of the prevention of micro- and macrovascular complications and correction of risk factors. Further research is needed on the effects of DF, taking into account the duration of use, doses, and various DF types and forms.